Pengaruh Metode Talking Stick Berbantuan Audio Visual terhadap Maharah Kalam - Masrifah, Nurriyatul; Sholihuddin, Ahmad (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah, IAIN Kediri, 2024)
This study aims to examine the implementation of the talking stick method supported by audio-visual media in improving the maharah kalam (speaking skills) of seventh-grade students at MTsN 2 Kota Blitar. Employing a quantitative approach with a quasi-experimental design, the study involved 35 students from class VII-A as the experimental group and 35 students from class VII-B as the control group. Research instruments included observation, tests, and documentation, with data analysis conducted through normality tests, homogeneity tests, and independent sample t-tests. The findings revealed that the average post-test score of the experimental group (81.4) was higher than that of the control group (77.2), with a t-value of 3.695 and a significance level of p = 0.001. These results indicate a significant difference between the two groups, leading to the conclusion that the talking stick method supported by audio-visual media positively influences students’ maharah kalam skills.